2008
DOI: 10.1073/pnas.0804904105
|View full text |Cite
|
Sign up to set email alerts
|

Pitx2 regulates gonad morphogenesis

Abstract: Organ shape and size, and, ultimately, organ function, relate in part to the cell and tissue spatial arrangement that takes place during embryonic development. Despite great advances in the genetic regulatory networks responsible for tissue and organ development, it is not yet clearly understood how specific gene functions are linked to the specific morphogenetic processes underlying the internal organ asymmetries found in vertebrate animals. During female chick embryogenesis, and in contrast to males where bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 48 publications
1
62
0
Order By: Relevance
“…Nodal establishes a large expression domain in the left lateral plate mesoderm (LPM) and induces the expression of Pitx2, a homeobox gene of the bicoid class (7). Pitx2 determines morphological L-R asymmetries in most organ systems (9-12) via modulation of cell-cell adhesion, cell morphology, extracellular matrix composition, spindle orientation, and cell proliferation (13)(14)(15).…”
mentioning
confidence: 99%
“…Nodal establishes a large expression domain in the left lateral plate mesoderm (LPM) and induces the expression of Pitx2, a homeobox gene of the bicoid class (7). Pitx2 determines morphological L-R asymmetries in most organ systems (9-12) via modulation of cell-cell adhesion, cell morphology, extracellular matrix composition, spindle orientation, and cell proliferation (13)(14)(15).…”
mentioning
confidence: 99%
“…Therefore, the higher prevalence of GCOC in the right ovary may be further elucidated by understanding the asymmetrical development of the gonads in the chicken. Regarding EOC, there is no evidence supporting a role for gonadal asymmetry in the prevalence of the disease in the right or left ovary (84); interestingly, however, paired-like homeodomain transcription factor 2 (PITX2), which is overexpressed in EOC, is also a key player in the asymmetric development of chicken female gonads (85,86). The expression of PITX2 in the left gonad promotes proliferation of the left cortex, leading to the asymmetric development of the gonads (85,87).…”
Section: Incessant Ovulation Hypothesismentioning
confidence: 99%
“…There is no further development of the right gonad and this leads to the formation of vestigial structures (Carlon and Stahl, 1985) or complete regression (Romanoff, 1960) at the adult stage. The molecular mechanism underlying asymmetrical development and the degeneration of the right ovary in female birds relies on PITX2 (Guioli and Lovell-Badge, 2007;Ishimaru et al, 2008;Rodriguez-Leon et al, 2008). Guioli and LovellBadge (2007) demonstrated that misexpression of Pitx2 in the right gonad using transfection with the RCAS retroviral vector is sufficient not only to induce symmetric development of the gonads but also to rescue the degeneration of the right ovary.…”
Section: Gonadogenesis and Left-right Asymmetry Of Embryonic Gonadsmentioning
confidence: 99%
“…Pitx2-knockout mice have abnormalities of internal organ asymmetry (Lin et al, 1999;Lu et al, 1999). Recently, Pitx2 was reported to play a role in embryonic gonad asymmetry in both sexes (Guioli and LovellBadge, 2007;Ishimaru et al, 2008;Rodriguez-Leon et al, 2008).…”
Section: Introductionmentioning
confidence: 99%